1999
DOI: 10.1007/s004390051155
|View full text |Cite
|
Sign up to set email alerts
|

Germline origins in the human F9 gene: frequent G:C→A:T mosaicism and increased mutations with advanced maternal age

Abstract: The factor IX gene (F9) is an advantageous system for analyzing recent spontaneous germline mutation in humans. Herein, the male:female ratio of mutation ("r") in F9 have been estimated by Bayesian analysis from 59 germline origin families. The overall "r" in F9 was estimated at 3.75. The "r"s varied with the type of mutation. The "r"s ranged from 6.65 and 6.10 for transitions at CpG and A:T to G:C transitions at non-CpG dinucleotides, respectively, to 0.57 and 0.42 for microdeletions/microinsertions and large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
5
19
1
Order By: Relevance
“…It was reported that maternal mosaicism accounts for a significant proportion of the origin of sporadic cases in hemophilia A [8][9][10]. Although systematic studies are limited for mosaicism in hemophilia B, there have been reports on the cases of mosaicism of F9 mutations [11][12][13][14][15]. In our previously reported series, sporadic cases accounted for 60% of Korean patients with hemophilia B [2], and a significant proportion of these cases could have been from maternal mosaicism.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It was reported that maternal mosaicism accounts for a significant proportion of the origin of sporadic cases in hemophilia A [8][9][10]. Although systematic studies are limited for mosaicism in hemophilia B, there have been reports on the cases of mosaicism of F9 mutations [11][12][13][14][15]. In our previously reported series, sporadic cases accounted for 60% of Korean patients with hemophilia B [2], and a significant proportion of these cases could have been from maternal mosaicism.…”
Section: Discussionmentioning
confidence: 80%
“…In sporadic hemophilia A, CpG transition point mutations from the maternal origin account for the majority of cases of somatic mosaicism [10]. On the other hand, non-CpG transition was the predominant type of mutation in sporadic hemophilia B not only originating from the mother, but also frequently traced up to either maternal grandmother or grandfather [11,12]. Thus, suspicion of the mosaicism is particularly relevant in a sporadic proband with hemophilia with transition point mutations.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, older females have a slightly higher likelihood of bearing a de novo germline mutation for haemophilia compared with younger females [23,38].…”
Section: Germline Cellmentioning
confidence: 82%
“…Current test methods may not pick up a low level of mosaicism in white cells. So far, in one series [19], mosaicism was proven in 13% of those individuals in whom mutations for haemophilia A originated, and in another series [23], in 11% of individuals in whom mutations for haemophilia B originated. Test methods for mosaicism are improving and leading to the identification of more mosaic individuals.…”
Section: Embryonic Cellmentioning
confidence: 97%
“…Tyr128 located in the epidermal growth factor 1 (EGF1) domain is a highly conserved residue. Three mutations at the analogous residue in FIX (p.Tyr115) had been described in hemophilia B [12][13][14]. It is likely that the introduction …”
Section: Discussionmentioning
confidence: 99%